It takes a family to lighten the load! The impact of family-to-business support on the stress and creativity of women micro-entrepreneurs in Sri Lanka. Issue 9 (8th April 2020) - Wijewardena, Nilupama; Samaratunge, Ramanie; Kumara, Ajantha Sisira; Newman, Alex; Abeysekera, Lakmal
Abstract : Purpose: The purpose of this paper is to examine whether family-to-business support acts as a job resource that attenuates the negative effects of work demands on the stress and creativity of women micro-entrepreneurs in the informal sector in Sri Lanka. Design/methodology/approach: Data from 359 women micro-entrepreneurs and their respective case officers in local government were used to test the hypothesized relationship between work demands and their creativity through the mediating mechanism of stress and the moderating effect of family-to-business support on the said relationship. Findings: Work demands reduced creativity through heightening the levels of stress faced by women micro-entrepreneurs. However, family-to-business support reduced the negative influence of work demands on creativity through stress. Practical implications: Women micro-entrepreneurs should build strong family ties to obtain support from family members. In addition, government training programs that target women micro-entrepreneurs should be extended to include their immediate family members. Originality/value: This paper contributes to the literature by examining whether family-to-business support buffers the negative effects of work demands for women micro-entrepreneurs in the informal sector. In doing so it makes a theoretical contribution by testing the key tenets of the JD-R model in entrepreneurial settings.